A spatiotemporal database prototype for managing volumetric surface management data in virtual GIS - Rahim, Mohd. Shafri. Mohd.; Shariff, A. R. M.; Mansor, Shattri; Mahmud, Ahmad Rodzi; Daman, Daut (Springer Berlin / Heidelberg, 2007)
Virtual GIS have the capability to present geographic features in three-dimension. This will contribute to increasing user understanding of phenomena that occurred in certain areas. Virtual GIS need to include temporal element in the system for managing dynamic phenomena to simulate real process. Spatiotemporal database system can be used to manage temporal data or spatial data that involve changes. In this paper, we present the database system of a spatiotemporal database prototype for managing volumetric surface movement; Volumetric Surface Movement Spatiotemporal Data Model that has the ability to store changes of the surface data of a three dimensional object. Formalization of the surface movement phenomena on the volumetric object were defined. This model has been implemented using relational database model which store only the changing points in order to ensure an efficient data management. We have developed a visualization tool with the database system to visualize movement on the surface. The prototype system of this model has been tested and found to be efficient